UMKM GO DIGITAL KAMPUNG BUANTAN LESTARI - Hutabarat, Sakti; Kurnia, Anita; Sinaga, Enjellika; Syahidah, Hafizhah Mardhiatus; Elmi, Imran; Jannah, Miftahul; Faturrahman, Muhammad Ikhsan; Sembiring, Nurfatta Bru; Hutagaol, Princess Restauli; Safitri, Rifda (FORDICATE, 2024)
Micro, Small and Medium Enterprises (MSMEs) of Buantan Lestari Village are active business activities both owned by individuals, groups, and business entities that meet the criteria as small and medium enterprises in Buantan Lestari Village. To increase the sales output of MSMEs requires the latest marketing methods. So KUKERTA UNRI students help in introducing digital marketing and providing technological guidance in making e-commerce accounts and how to use e-commerce in digital marketing. The objective of the "UMKM GO DIGITAL" program is to promote economic growth in Buantan Lestari Village by facilitating MSME products through the digital market to generate a large market share. The method used is by conducting socialization about digital marketing and technology guidance. This activity was successfully carried out and produced an online shop to sell MSME products in Buantan Lestari Village.